The Complex Resource-Based View: Implications for Theory and Practice in Strategic Human Resource Management - Colbert, Barry A. (Academy of Management Review, 2004)
Barry A. Colbert, The Complex Resource-Based View: Implications for Theory and Practice in Strategic Human Resource Management, The Academy of Management Review, Vol. 29, No. 3 (Jul., 2004), pp. 341-358